Matematyka
Amalek
2017-06-27 01:40:29
1 3/8-2(9/8-2 5/6) b 3/16*(-2 2/3)-3(1/6+3/4)
Odpowiedź
111nika
2017-06-27 05:01:09

1 i 3/8 - 2 ·(9/8 - 2 i 5/6) = 1 i 3/8 - 2·(27/24 - 2 i 20/24) = = 1 i 3/8 -2 ·(27/24 - 68/24) = 1 i 3/8 - 2 ·(-41/24) = 1 i 3/8 +41/12) = = 1 i 3/8 +3 i 5/12 = 1 i 9/24 +3 i 10/24 = 4 i 19/24 3/16 ·(-2 i 2/3) - 3·(1/6+3/4) = 3/16 ·(-8/3) - 3·(2/12+9/12) = = -1/2 - 3 · 11/12 = -1/2 - 11/4 = -2/4 - 11/4 = -13/4 = -3 i 1/4

CocoChannel
2017-06-27 05:02:24

1 3/8-2(9/8-2 5/6) = 11/8 - 2*( 9/8 - 17/6) = 11/8 - 18/8 + 34/6= 66/48 - 108/48 + 272/48 = -42/48 + 272/48 = 230/48= 115/24 = 4 19/24  ----  3/16*(-2 2/3)-3(1/6+3/4) = 3/16 *( -8/3) -3 * (1/6+3/4)= -24/48 - 3 *(4/24+18/24) = -1/2 - 3* 22/24 = -1/2 - 66/24= -1/2 - 11/4 = -2/4 - 11/4 = -13/4 = - 3 1/4 

Dodaj swoją odpowiedź